Assessing the therapeutic impact of resveratrol in ALS SOD1-G93A mice with electrical impedance myography - Nagy, Janice A.; Semple, Carson; Lo, PuiChi; Rutkove, Seward B. (Frontiers in Neurology, 2022)
To aid in the identification of new treatments for amyotrophic lateral sclerosis (ALS), convenient biomarkers are needed to effectively and uniformly measure drug efficacy. To this end, we assessed the effects of the nutraceutical resveratrol (RSV) on disease onset and overall survival in SOD1-G93A (ALS) mice and compared several standard biomarkers including body mass, motor score (MS), paw grip endurance (PGE), and compound motor action potential (CMAP) amplitude, with the technique of electrical impedance myography (EIM) to follow disease progression. Eighteen ALS mice (nine females, nine males) received RSV in the chow (dose: 120 mg/kg/day) starting at 8 weeks of age; 19 ALS mice (nine females, 10 males) received normal chow; 10 wild type (WT) littermates (five females, five males) fed standard chow served as controls. Biomarker assessments were performed weekly beginning at 8 weeks. No differences in either disease onset or overall survival were found between RSV-treated and untreated ALS mice of either sex; moreover, all biomarkers failed to identify any beneficial effect of RSV when administered at this dose. Therefore, for the comparative evaluation of the ability of the various biomarkers to detect the earliest symptoms of disease, data from all animals (i.e., RSV-treated and untreated ALS mice of both sexes) were combined. Of the biomarkers tested, EIM impedance values, i.e., surface EIM longitudinal phase at 50 kHz (LP 50 kHz), and CMAP amplitude showed the earliest significant changes from baseline. LP 50 kHz values showed a rate of decline equivalent to that of CMAP amplitude and correlated with both PGE and CMAP amplitude [Spearman rho = 0.806 (p = 0.004) and 0.627 (p = 0.044), respectively]. Consistent with previous work, these findings indicate that surface EIM can serve as an effective non-invasive biomarker for preclinical drug testing in rodent models of ALS.